2018
DOI: 10.1155/2018/2065491
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Efficiency of a Decision Support System through the Clustering of Complex Rule‐Based Knowledge Bases and Modification of the Inference Algorithm

Abstract: Decision support systems founded on rule-based knowledge representation should be equipped with rule management mechanisms. Effective exploration of new knowledge in every domain of human life requires new algorithms of knowledge organization and a thorough search of the created data structures. In this work, the author introduces an optimization of both the knowledge base structure and the inference algorithm. Hence, a new, hierarchically organized knowledge base structure is proposed as it draws on the clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In papers [8], and [7], we devoted attention to describing the AHC algorithm and its application to such specific data as rules in knowledge bases [5]. It's worth recalling that the clustering flow can be different depending on the clustering method we used.…”
Section: Clustering and Outlier Mining In Rulesmentioning
confidence: 99%
“…In papers [8], and [7], we devoted attention to describing the AHC algorithm and its application to such specific data as rules in knowledge bases [5]. It's worth recalling that the clustering flow can be different depending on the clustering method we used.…”
Section: Clustering and Outlier Mining In Rulesmentioning
confidence: 99%
“…The previous research work of the authors showed that, instead of searching whole with all rules, we usually only search a small piece of it (the experiments showed that usually only a few percent of the total set was reviewed). More about this can be found in [ 5 , 6 ]. Rule clustering allows for the user to browse the faster.…”
Section: Rule Clusteringmentioning
confidence: 99%
“…We want our solution to be universal and, therefore, to work effectively both for data with outliers and for typical data. We also want our solution to be effective for any data type, not just only numerical, which is easier to analyze [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%